PERBEDAAN PENGUNAAN MEDIA BERBASIS KOMPUTER TERHADAP MINAT DAN HASIL BELAJAR KIMIA DI SMAN 1 WAMENA - AMBARWATI, UTAMI; SIREGAR, TIURLINA (Jurnal Ilmu Pendidikan Indonesia, 2018)
The purposesof this research are (1) to know is there any difference on study interest between class who apply media based non computer with class who did not (2) to know is there any differences student’s result between class who apply media base on computer with class who did not (3) to know is there any improvement on student’s study result between class who apply media base on computer with class who did not. The population on this research is all student in class X odd semester in the year of 2012/2013 SMAN1 Wamena with the student’s 450. The sample that is used is student’s in class X A as an experiment class and class X B as control class. The collection data did by using test on study result and questionaire. Technique of data analysis used SPSS 16. The nominal result shows that nGrain experiment 0,6 and nGrain control is 0,4 the significan counting is > 0,05 and data is normal. The result homogeneityshow sig count is > 0,05 significance so both of these group have some variant or homogeny. The result of hypothesis test (test t) sig count is <0,05 achieve Ha and reject Ho. The result of this research are (1) There is any difference on student’s interest between class who used media based on computer and class who did not (2) There is any significant difference on study result between who used media based on computer and class who did not (3) Student’s study result in class who used media base on computer is improve rather that class who did not. Keywords : Media Base on Computer, Learning Interest, Study Result, Hydrocarbon